TOWARDS DRAFTING ARTIFICIAL INTELLIGENCE (AI) LEGISLATION IN SOUTH AFRICA - Sizwe Snail Ka Mtuze (Obiter, 2024)
Artificial Intelligence also abbreviated as “AI” has been the subject of much legal debate and legal writing. This article seeks to identify internationally accepted AI principles and norms that are contained in the South African Constitution. This article also seeks to identify policy such as the PC4IR Report and legislation that regulates and accommodates the use of AI in South Africa. What emerges clearly is that there has never been a deliberate attempt to legislate AI, and that the legislation referred to is applicable by coincidence not intention. The article goes on to highlight African and BRICS policies and best practices on AI, European best practices and legal norms and values on AI, and the draft EU AI Act. The article concludes with a recommendation that South Africa introduce AI legislation as a matter of urgency.